Benefit Corporation Legislation and the Emergence of a Social Hybrid Category. (May 2015) - Rawhouser, Hans; Cummings, Michael; Crane, Andrew
Previous research highlights tensions that social hybrids face by spanning categories. This article explores the emergence of legislation to support a new category for social hybrids, focusing on Benefit Corporation legislation in the United States. It presents quantitative analysis of state-level factors that make a state suitable for a social hybrid category (attractiveness for for-profit business and nonprofits, existing social hybrid organizations, legislative intensity, and political leanings) followed by qualitative analysis of the arguments marshaled for the creation of the Benefit Corporation legal form. These findings raise important insights for research on social hybrids and suggest a range of practical implications.